2018
DOI: 10.1002/gcc.22669
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length, telomerase reverse transcriptase promoter mutations, and melanoma risk

Abstract: Telomere repeats at chromosomal ends, critical for genomic integrity, undergo age-dependent attrition and telomere length has been associated with different disorders including cancers. In this study, based on 1469 patients and 1158 healthy controls, we show a statistically significant (P = 6 × 10 ) association between increased telomere length and melanoma risk. Mendelian randomization, using 5 telomere length-associated polymorphisms, ruled out confounding factors or reverse causality and showed association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 52 publications
4
58
0
1
Order By: Relevance
“…However, our data show that increased TERT expression in BCC tumors can be primarily attributed to the promoter mutations as shown in adult gliomas 37 . Telomeres in tumors with the TERT promoter mutations are usually shorter than in tumors without those mutations as observed in melanoma and gliomas 35,38 . However, we did not observe a statistically significant difference in telomere length in BCC tumors.…”
Section: Discussionmentioning
confidence: 98%
“…However, our data show that increased TERT expression in BCC tumors can be primarily attributed to the promoter mutations as shown in adult gliomas 37 . Telomeres in tumors with the TERT promoter mutations are usually shorter than in tumors without those mutations as observed in melanoma and gliomas 35,38 . However, we did not observe a statistically significant difference in telomere length in BCC tumors.…”
Section: Discussionmentioning
confidence: 98%
“…The associations between the instrument-outcome were estimated using logistic regression at the allele levels in the study population. A one-sample MR study was conducted using non-overlapping datasets in the same population (33). Two datasets were generated for cases and controls based on similar mean and variance for arsenic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The observational studies have consistently shown statistically significant associations between long telomeres and increased cancer risk (27,35,36). The genetic basis for those observations are provided by the studies showing that various polymorphisms that modulate telomere length also affect the risk of different cancers, with alleles segregating with increased telomere length associating with increased risk (10,11,37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations